Beyond surveillance: privacy, ethics, and regulations in face recognition technology - Wang, Xukang; Wu, Ying Cheng; Zhou, Mengjie; Fu, Hongpeng (Frontiers in Big Data, 2024)
Facial recognition technology (FRT) has emerged as a powerful tool for public governance and security, but its rapid adoption has also raised significant concerns about privacy, civil liberties, and ethical implications. This paper critically examines the current rules and policies governing FRT, highlighting the tensions between state and corporate interests on one hand, and individual rights and ethical considerations on the other. The study also investigates international legal frameworks aimed at protecting individual rights and privacy, arguing that current legislative measures often fall short of robust scholarly standards and international human rights norms. The paper concludes with recommendations for developing principled and adaptable governance frameworks that harness the benefits of FRT while mitigating its risks and negative impacts, underscoring the importance of placing human rights and ethics at the center of regulating this transformative technology.